2022
DOI: 10.1523/jneurosci.2257-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsal Visual Pathway Represents Object-Centered Spatial Relations for Object Recognition

Abstract: Although there is mounting evidence that input from the dorsal visual pathway is crucial for object processes in the ventral pathway, the specific functional contributions of dorsal cortex to these processes remain poorly understood. Here, we hypothesized that dorsal cortex computes the spatial relations among an object's parts -a processes crucial for forming global shape perceptsand transmits this information to the ventral pathway to support object categorization. Using fMRI with human participants (females… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 105 publications
3
29
1
Order By: Relevance
“…Accordingly, it is possible that the enhanced FCPN and DAN engagement during recognized trials reflect attention-related modulations that support object recognition 48,49 . Alternatively, given the increasing evidence that FCPN and DAN regions are actively involved in object recognition processing 11,12,50,51,52 , the enhanced FCPN and DAN engagement may be directly related to perceptual processing per se. For example, the early recognition-related responses in the FPCN and DAN may reflect an initial, fast analysis of noisy visual input in the dorsal visual stream which facilitates fine-grained analysis happening in the ventral stream 6,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is possible that the enhanced FCPN and DAN engagement during recognized trials reflect attention-related modulations that support object recognition 48,49 . Alternatively, given the increasing evidence that FCPN and DAN regions are actively involved in object recognition processing 11,12,50,51,52 , the enhanced FCPN and DAN engagement may be directly related to perceptual processing per se. For example, the early recognition-related responses in the FPCN and DAN may reflect an initial, fast analysis of noisy visual input in the dorsal visual stream which facilitates fine-grained analysis happening in the ventral stream 6,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, decoding in occipital cortex preceded the ventral pathway and occipital cortex was a significant predictor of the time-varying responses of the ventral pathway. Importantly, TMS and fMRI studies suggest that the coarse information transmitted by the magnocellular pathway is sufficient to compute an object’s global shape structure (Wang et al, 2022), and that this information can support decoding of object category in the dorsal pathway (Ayzenberg & Behrmann, 2022b). Furthermore, studies have shown that such structural information may then be transmitted to the ventral pathway to support object recognition (Ayzenberg & Behrmann, 2022b; Bar et al, 2006; Kveraga, Boshyan, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, TMS and fMRI studies suggest that the coarse information transmitted by the magnocellular pathway is sufficient to compute an object’s global shape structure (Wang et al, 2022), and that this information can support decoding of object category in the dorsal pathway (Ayzenberg & Behrmann, 2022b). Furthermore, studies have shown that such structural information may then be transmitted to the ventral pathway to support object recognition (Ayzenberg & Behrmann, 2022b; Bar et al, 2006; Kveraga, Boshyan, et al, 2007). Thus, the earlier decoding of object category in the dorsal pathway may be explained by privileged magnocellular input.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations